Análise do setor de planos de saúde: um estudo de caso com operadoras do Rio de Janeiro - Pacheco, José Luciano Costa (2005)
The present study shows, based on the evaluation of the health plans regulation - which started after the approval of law 9656/98 in the second semester or 1998, analysis conducted from 1994 to 1998, before the regulation took place and after that, from 1999 to 2004. Based on the analysis of the strengths that rule that sector, where Porter’s five-strength tool was used, it was concluded that its level of attractiveness is currently low, which partly explains the lack of interest from international investors. Behavior aspects of the system ‘s main players were also analyzed and have revealed the existing lack of confidence among operators and medical/hospital service providers, as well as the negative consequences of this conflicting worn out relationship for the whole society. Comparative analysis between the unruly market and the post-regulatory period was also conducted and the assumption that the regulated market has brought more positive than negative aspects was confirmed. An action plan was developed starting from the analysis of the main symptoms and causes associated to both situational and structural aspects. The central suggestion calls for redirecting the operators’ strategies for client retaining, once the health plan market finds itself in retraction, with weak demand for new consumers. Other relevant aspect identified in this research is related to ethical principals. Operators must revise their relationship with hospital/medical service providers and brokers in order to priorise long term relationships and, among the suggested actions, reconsider existing rewarding policies towards them